Intensity plot depicting the relationship between transmission and wavelength for duty cycles between 0 - 100% - Barrington, James (Cranfield University, 2018)
The folder contains 200 text files where each 10 files is an increase in 5% UV irradiated duty cycle from 5 - 100%. Each text file is arranged into 2 tab delimited columns of wavelength and intensity. This is the raw data associated with our paper 'The effect of UV irradiation duty cycle on the transmission spectra of optical fiber long period gratings'
Keywords: optical fibre sensors'; 'Long period gratings'; 'Optical Physics not elsewhere classified'